UMKM Sebagai Peningkatan Pembangunan Ekonomi Bangsa Indonesia - Utami, Astri Putri; Rahmahita, Arista; Dermawan, Deris (Jurnal Manajemen Akuntansi (JUMSI), 2022)
Progress in today's globalized world is often measured by economic success, making it a leading indicator for government spending. MSMEs play an important role in national economic development, especially economic development (MSMEs). Strategic importance is placed on the role played by MSMEs in the national economy. The reason for this Indonesian economic trend is thought to come from the rise of MSMEs there. After the 2008 financial crisis, SMEs and MSMEs continued to grow. This is another proof that SMEs can weather the current economic storm. In addition, the National SME sector has become a major employer. The MSME industry has the potential to boost household income thanks to the many jobs created. For this reason, SMEs are given an important role to play in the fight against poverty and unemployment. The government continues to encourage MSMEs by providing them with the means they need to succeed so that they can fulfill their role as the backbone of the creation of the national economy. Growth must include the role of the community as a driver and prioritize the development of a sense of belonging and community. Welfare improvement is one of the benchmarks of a country's progress. It is very important for a country to focus on economic growth in order to grow its people's per capita income and standard of living.